2012
DOI: 10.1016/j.clinbiomech.2011.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Describing the active region boundary of EMG-assisted biomechanical models of the low back

Abstract: Background: Electromyography-assisted (EMG-assisted) biomechanical models are used to characterize the muscle and joint reaction forces in the lumbar region. However, during a fullrange trunk flexion, there is a transition of extension moment from the trunk extensor muscles to the passive tissues of the low back, indicating that the empirical EMG data used to drive these EMG-assisted models becomes less correlated with the extensor moment. The objectives of this study were to establish the trunk flexion angles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…As the load on posterior lumbar tissues is increased the angle of trunk flexion also increases, whether statically or in repetitive cyclic movements (Dickey et al 2003;McGill & Brown1992). The increase in trunk flexion causes the lumbar tissues to become the dominant load bearers (Ning & Mirka, 2012). These repetitive loading schemes reduce the posterior viscoelastic tissue tension independent of muscular fatigue or external load applications (Olson).…”
Section: Discussionmentioning
confidence: 99%
“…As the load on posterior lumbar tissues is increased the angle of trunk flexion also increases, whether statically or in repetitive cyclic movements (Dickey et al 2003;McGill & Brown1992). The increase in trunk flexion causes the lumbar tissues to become the dominant load bearers (Ning & Mirka, 2012). These repetitive loading schemes reduce the posterior viscoelastic tissue tension independent of muscular fatigue or external load applications (Olson).…”
Section: Discussionmentioning
confidence: 99%
“…During trunk bending, a transition of load from lumbar active muscles (e.g. lumbar extensor muscles) to lumbar passive tissues (ligaments, fascia discs, bone, and non-contractile component of muscles) occurs at deeper trunk flexion postures (Ning et al, 2011;Ning et al, 2012), which demonstrates the synergy between lumbar active muscles and passive tissues. Studies have suggested that this transition of load indicates that the tension generated by passive tissue stretching was adequate to counterbalance the external moment acting on the lumbar spine, therefore allowing lumbar extensor muscles to cease activation (Solomonow et al, 2003;Floyd and Silver, 1951;Allen, 1948).…”
Section: Lumbar Tissues Load Sharing Mechanism 231 Flexion-relaxatimentioning
confidence: 99%
“…the contractile component of muscles) and passive tissues (ligaments, fascia discs, bone, and non-contractile component of muscles). During forward trunk bending, a transition of load from lumbar active tissues to passive tissues occurs at deeper trunk flexion postures (Ning et al, 2011;Ning et al, 2012). This load shifting demonstrates the synergy between lumbar active and passive tissues and was termed as flexion relaxation phenomenon (FRP) by Silver (1951, 1955).…”
Section: List Of Acronymsmentioning
confidence: 99%
See 2 more Smart Citations